Transmission of Financial Stress in Europe : The Pivotal Role of Italy and Spain, but not Greece - Gonzalez-Hermosillo, Brenda (IMF Working Papers; Working Paper ;, 2014)
This paper proposes a stochastic volatility model to measure sovereign financial distress. It examines how key European sovereign credit default swap (CDS) spreads affect each other; specifically, the paper analyses the volatility structure of Germany, Greece, Ireland, Italy, Spain and Portugal. The stability of Germany is a close proxy for the resilience of the euro area as markets use Germany's sovereign CDS as a hedge for systemic risk. Although most of the CDS changes for Germany during 2009-12 were due to idiosyncratic factors, market developments in Italy and Spain contributed significantly, likely due to their relative importance in the region. Changes in Greece's sovereign CDS had no significant effect on Germany's sovereign CDS despite initial widespread concerns about such linkages. Spain and Italy show a notable co-dependence in explaining each other's volatility while Germany also plays an important role. It is found that extreme bad news led to persistent and nearly permanent effects on the stochastic volatility of European sovereign CDS spreads.